Mengoptimalkan Efisiensi Anggaran Birokrasi : Tantangan dan Solusi - Awaliyah Matondang, Khairani; Syaqinah Ujung; Syakura Annuradi, M. Abdan; Agustine Situmorang, Elsa Aurel (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The bureaucratic budget is an important aspect in managing a country's government. Efficiency in bureaucratic budget management is very important in ensuring that public resources are used as well as possible. This research uses qualitative, descriptive methods which tend to use analysis that focuses on in-depth observation. The findings of this research are that there are challenges in optimizing bureaucratic budget efficiency, including high operational costs, lack of accountability and transparency, budget uncertainty, and ineffective policies. . Thus, to overcome these challenges, there are solutions that can be implemented such as the use of technology, increasing transparency, long-term budget planning, program and policy evaluation, bureaucratic reform, and collaboration with the private sector and NGOs.